EFFECT OF ORGANIZATIONAL BEHAVIOR AND ORGANIZATIONAL CLIMATE ON EMPLOYEE JOB SATISFACTION IN PT. EAGLE INDO PHARMA - Siahaan, Lydia Irene; Imran, Ayub Ilfandy; Diniati, Anisa (Advances in Social Sciences Research Journal, 2021)
This research was conducted to determine the impact of organizational behaviour and organizational climate on employees’ satisfaction at PT. Eagle Indo Pharma. This research uses quantitative methods with descriptive-causal research that uses the principle of positivism. The sampling technique used is probability sampling by taking 83 employees as a sample in this study. The data obtained in this study is by distributing questionnaires through Google Form. The questionnaire contains 33 statement items with a Likert measurement scale. Based on the test results, it was found that there was a positive and significant influence on employee organizational behaviour on employee job satisfaction, there was a positive and significant influence on employee organizational climate on employee job satisfaction and there was a positive and significant influence on organizational behaviour and organizational climate together on employee job satisfaction. Organizational climate has a greater influence (on employee job satisfaction) than organizational behaviour. The quality of organizational behaviour and organizational climate together contribute to job satisfaction by 54.4% (= 0.544x 100%). While the remaining 45.6% is influenced by other variables which are not discussed in this study. Based on the value processed from the hypothesis test or t test, that the signification t 0.000 < 0.05 and the thitung value (X1) 2.036 > ttabel 1.990 and thitung value (X2) 4.216 > ttabel 1.990. Hence, it can be interpreted that H0 is rejected and H1 and H2 are accepted that there is a significant impact among variable X1 (Organizational Behaviour) and variable X2 (Organizational Climate) on variable Y (Job Satisfaction) in PT. Eagle Indo Pharma.